⁷Be generation in the reaction of two-particle photodisintegration of ¹⁴N nucleus - Glaznev, M.S.; Gorbenko, E.S.; Bespalov, A.L.; Murtazin, R.T.; Khodyachikh, A.F. (Вопросы атомной науки и техники, 2014)
The reaction of two-particles nitrogen nucleus photodisintegration with ⁷Li and ⁷Be in the final state are investigated using diffusion chamber, which is placed into the magnetic field and filled with 15% nitrogen and helium compound. Chamber was irradiated with gamma rays from electron accelerator. The method of extraction of the reaction from the background two-particle reactions with multi-charged ions in the final state was created. Differential, full and integral cross-section of the reaction were measured. The results were compared with experimental data, where the full isotope ⁷Be output at ¹⁴N photodisintegration reaction was measured